Raising Students Awareness to Climate Change: An Illustration With Binding Communication. (April 2017) - Parant, Aymeric; Pascual, Alexandre; Jugel, Milena; Kerroume, Myriam; Felonneau, Marie-Line; Guéguen, Nicolas
Much energy and money is dedicated to increasing climate change awareness and pro-environmental behaviors. Mere communication campaigns, which are often alarmist, are widely used despite their uncertain effectiveness. We suggest that using binding communication strategies would prove more adequate. Binding communication consists in combining a persuasive message and a preparatory act linked to the persuasive message. This procedure is generally reported to be more efficient than a single persuasive message at influencing attitudes and behavior. This hypothesis was tested in a study in which students were presented with a classic climate change communication with/without a preparatory act (participant-proposed solutions). Results showed that although knowledge about climate change increased in both conditions, attitudes and behavior follow-through were positively affected only in the binding communication condition. Therefore, in addressing climate change and global warming behaviors, pairing a persuasive message with personal solution generation is a potentially valid and useful technique.